Navigating the digital seas: Legal challenges and global governance of maritime cyber operations - Jin, Yongming; Feng, Yuan; Liu, Chaomin; Li, Shibo (Frontiers in Marine Science, 2025)
Rapid digitization of the maritime sector has heightened its exposure to cyber threats, calling for a reexamination of international legal frameworks. This study examines how the United Nations Convention on the Law of the Sea (UNCLOS) could be adapted or supplemented to govern emerging Maritime Cyber Operations (MCOs) more effectively. Using a multi-level governance perspective that integrates legal analysis and case studies, we identify critical gaps in UNCLOS and related maritime law. UNCLOS currently struggles with unresolved jurisdictional ambiguities across territorial seas, exclusive economic zones (EEZs), and the high seas. There is also persistent uncertainty about whether cyberattacks qualify as ‘uses of force’ under international law, and existing enforcement mechanisms are ill-equipped to address cyber operations by state or non-state actors. Although soft-law efforts like the Tallinn Manual 2.0 provide helpful interpretative guidance, they lack binding authority and broad consensus. Additionally, ongoing technical vulnerabilities in crucial maritime infrastructure—from port automation systems to undersea communication cables—further compound these governance challenges. To confront these issues, this paper proposes an integrated multi-level governance approach. It recommends updating UNCLOS (potentially via a supplementary protocol), adopting industry-wide cybersecurity standards, and strengthening both regional and international cooperation. By bridging the legal and technical aspects of maritime cybersecurity, the study offers policymakers a structured set of practical strategies. This framework is intended to lay a foundation for future policy that addresses urgent maritime security needs while preserving the efficiency of global maritime commerce in an increasingly digital world.